Agxt2l-mediated glycerophospholipid metabolism in trophocytes explains Apis mellifera queen’s higher oviposition over A. cerana - Luxia Pan; Zilong Wang; Shiqing Zhong; Tianyu Xu; Weixuan Chen; Fuping Cheng; Zhijiang Zeng (Communications Biology)
Abstract Apis mellifera and Apis cerana are two important honey bee species widely kept and studied. But their queens differ greatly in egg-laying capacity. To determine the mechanisms of this difference, we compare gene expression, chromatin accessibility and spatial localization of differential genes in the ovaries of the two species in virgin queens and laying queens using ATAC-seq, RNA-Seq, homologous gene alignment and spatial transcriptome. The results reconfirm that the egg-laying capability of A. mellifera queens is significantly higher than that of A. cerana queens. The chromatin accessibility and nutrient cells ratio of A. mellifera queens are higher than those of A. cerana queens. Further investigations reveal that agxt2l (LOC408817) is significantly over-expressed in the ovaries of A. mellifera queens compared to A. cerana queens and is crucial for ovary development. Moreover, agxt2l can increase the phospholipid content in ovarian nutrient cells through the glycerophospholipid metabolism pathway to promote embryo formation and is regulated by brc-z1 (LOC552255). These findings suggest that the brc-z1-agxt2l signal pathway causes increased egg-laying in the queens of A. mellifera compared to the queens of A. cerana by accelerating lipid synthesis due to heightened glycerophospholipid metabolism.